1982
DOI: 10.3758/bf03204183
|View full text |Cite
|
Sign up to set email alerts
|

Physical and cognitive dimensions in stimulus comparison

Abstract: Two experiments were carried out using a same-different task with sets of four stimuli varying orthogonally in three dimensions. Sameness was defined by each of the three dimensions in turn, as well as by physical identity. Two types of dimensions, physical and cognitive, were studied. In Experiment 1, the numerals 6, 10, VI, and X, which vary in Length, System, and Name, were used. With simultaneous presentation, order of difficulty was from the physical dimension of Length to the cognitive dimension of Name.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…As Santee and Egeth (1980) noted, these results have been obtained with dimensions that have been shown to be separable from results from classification tasks. For different stimulus pairs, the results have been very inconsistent, ranging from an increase in RT with irrelevant disparity (e.g., Larsen & Bundesen, 1978), to a decrease in RT (e.g., Garner, Podgorny, & Frasca, 1982), to no effect or an inconsistent effect (e.g., Dixon & Just, 1978).…”
Section: Integrality With Stimulus Comparisonmentioning
confidence: 99%
“…As Santee and Egeth (1980) noted, these results have been obtained with dimensions that have been shown to be separable from results from classification tasks. For different stimulus pairs, the results have been very inconsistent, ranging from an increase in RT with irrelevant disparity (e.g., Larsen & Bundesen, 1978), to a decrease in RT (e.g., Garner, Podgorny, & Frasca, 1982), to no effect or an inconsistent effect (e.g., Dixon & Just, 1978).…”
Section: Integrality With Stimulus Comparisonmentioning
confidence: 99%
“…Gamer, Podgorny, and Frasca (1982) defined stimulus dimensions on a continuum from physical to cognitive, such that a pair to be compared could be defined as same on a physical versus a more arbitrary (learned) dimension. They found that when the sameness rule was cognitive, there was no fast-same effect (nonsignificant 1D-msec advantage for same stimuli in Experiment 1A and a nonsignificant 6-msec fast-different effect in Experiment 2).…”
mentioning
confidence: 99%
“…Garner, Podgorny, and Frasca (1982) recently carried out a set of experiments to determine whether a stimulus name functions in the same way that physical attributes do. Although their research was not directly concerned with perceptual learning, we used their fmdings to study this problem in terms of the selective attention paradigm that has been used to study the interaction of various kinds of stimulus attributes (e.g., Garner, 1978;Garner & Felfoldy, 1970;Pomerantz & Garner, 1973).…”
mentioning
confidence: 99%
“…The stimulus set used by Garner et al (1982) is useful for studying perceptual learning because it is described by physical and cognitive stimulus dimensions. A physical dimension is one on which the physical properties of the stimuli are adequate for carrying out a task, whereas a cognitive dimension is one on which the physical properties are insufficient to accomplish a task, so that the subject has to make his judgment using a learned association.…”
mentioning
confidence: 99%
See 1 more Smart Citation